DEVELOPING VIRTUAL TOUR REALITY–BASED LEARNING MEDIA FOR INTRODUCING THE LOCAL CULTURAL SITE OF THE PUTRI PUKES CAVE FOR YOUNG LEARNERS - Sapitri, Eliza; Fitriani, Dewi; Umar bin Abd Aziz; M.Pd, Umar bin Abd Aziz (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2026)
Introducing local culture to early childhood requires engaging and contextual learning media. The limited availability of learning media capable of visually and interactively presenting local cultural objects poses a challenge for teachers in introducing such local culture. This research aims to develop Virtual Tour Reality (VTR)-based learning media for early childhood children to introduce the local culture of Putri Pukes Cave located in Central Aceh. This study employs the Research and Development method with the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. The research involved 1 subject matter expert validator and 1 media expert validator, and was trialed with 39 children aged 5-6 years. The learning media was developed using the 360 Sphere Camera Foxpoi application and Lapentor software, which can be accessed via mobile phones and laptops. The results indicate validation feasibility scores of 90% from the subject matter expert, 82.5% from the media expert, and a child response test score of 90%; thus, the VTR learning media is deemed highly suitable for use as a learning medium to introduce the local culture of Gua Putri Pukes to early childhood learners.